2020
DOI: 10.1080/07448481.2020.1841776
|View full text |Cite
|
Sign up to set email alerts
|

Life events, depression and supportive relationships affect academic achievement in university students

Abstract: Life events, depression and supportive relationships affect academic achievement in university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Currently, it is estimated that the number of individuals suffering from depression may be higher than 350 million (Aryani & Kurniawan, 2020 ). It is well known that depression may reduce life quality (Erbay et al, 2021 ; Luseno et al, 2021 ), academic achievement (Schrack et al, 2021 ; Spence et al, 2020 ) and job performance (Parent‐Lamarche et al, 2020 ). Moreover, depression may be considered a predisposing factor in both substance addictions (Howe et al, 2021 ) and behavioural addictions (Çıkrıkçı, 2019 ; Young & Rogers, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is estimated that the number of individuals suffering from depression may be higher than 350 million (Aryani & Kurniawan, 2020 ). It is well known that depression may reduce life quality (Erbay et al, 2021 ; Luseno et al, 2021 ), academic achievement (Schrack et al, 2021 ; Spence et al, 2020 ) and job performance (Parent‐Lamarche et al, 2020 ). Moreover, depression may be considered a predisposing factor in both substance addictions (Howe et al, 2021 ) and behavioural addictions (Çıkrıkçı, 2019 ; Young & Rogers, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…These conceptualizations in the literature form the basis for the investigations of depression in this study. Prior literature indicated that depressive disorders had damaging impacts on student development, especially on their academic performance (Andrews & Wilding, 2004; Goodwin, 2020; Hysenbegasi et al, 2005; Spence et al, 2020). However, little is known about the influence of depression on the motivational system of college students, which raised great concern in the field of personality psychology (Elliot & Thrash, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for most Chinese adolescents, the CEE induces the highest stress level, which could have an inevitable negative impact on the health of these adolescents. Evidence shows that life event in the past year of middle school would influence the relationship between negative emotion and academic performance of youth (27). And at the same time, CEE would bring other problem in adolescences.…”
Section: Introductionmentioning
confidence: 99%